Media Instagram sebagai Media Publikasi Karya Mahasiswa DKV ISI Surakarta di Masa Pandemi Covid-19 - Farhatin, Naily; Pratiwi, Fajri Rahma; Farid, Farid (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
This study aims to determine the benefits of using social media, especially Instagram as a medium for exhibitions of work by ISI Surakarta students during the pandemic. The data collection process was carried out by observing the behavior of the community during the pandemic and also interviewing several art activists who often publish their work on Instagram. The material obtained from observations and interviews was transcribed and analyzed. The results of the analysis raise 3 themes that are discussed here, namely: the use of social media Instagram in everyday life, Utilizing social media Instagram as a place to show off the work of ISI Surakarta students, stages, and parties who have a big influence to participate so that this event takes place. The study of the three themes is very useful to understand how to optimally improve the ability to work and utilize various social media as a forum to publish the results of his works during the pandemic period, where you cannot do real activities, you have to go through virtual ones.